Altitude training for elite endurance athletes: A review for the travel medicine practitioner - Flaherty, G.; O´Connor, R.; Johnston, N. (Travel Medicine and Infectious Disease, 2016)
High altitude training is regarded as an integral component of modern athletic preparation, especially for endurance sports such as middle and long distance running. It has rapidly achieved popularity among elite endurance athletes and their coaches. Increased hypoxic stress at altitude facilitates key physiological adaptations within the athlete, which in turn may lead to improvements in sea-level athletic performance. Despite much research in this area to date, the exact mechanisms which underlie such improvements remain to be fully elucidated. This review describes the current understanding of physiological adaptation to high altitude training and its implications for athletic performance. It also discusses the rationale and main effects of different training models currently employed to maximise performance. Athletes who travel to altitude for training purposes are at risk of suffering the detrimental effects of altitude. Altitude illness, weight loss, immune suppression and sleep disturbance may serve to limit athletic performance. This review provides an overview of potential problems which an athlete may experience at altitude, and offers specific training recommendations so that these detrimental effects are minimised.